A design evaluation of the National Policy on Climate Change of Zambia: Awareness as an effective tool to mitigate climate change - Kaoma-Sikaneta, Chibemba Hope (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPA)--Stellenbosch University, 2020.